2019
DOI: 10.29309/tpmj/2019.26.12.3131
|View full text |Cite
|
Sign up to set email alerts
|

Vesicovaginal Fistula (VVF): Success of primary repair.

Abstract: Objectives: The main objective of this research is to determine success of primary repair of vesicovaginal fistula at tertiary care hospital. Study Design: Quasi Experimental. Setting: DHQ Hospital, Faisalabad, Obstetrics and Gynaecology Department. Period: From Mar 2015 to Mar 2017. Material & Method: 15 patients were enrolled by consecutive sampling and those having fistulas more than 4cm or involving ureteric orifice, bladder neck or urethra were excluded. After proper history examination, preliminary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They determined success rate of 93.3% by primary repair of VVF by Transabdominal and transvaginal route combined. 19 A study conducted in UK concluded that there is no difference in success rate of VVF repair done via any one of two approaches transabdominal or transvaginal approach and transvaginal approach is more cost effective than transabdominal approach. 20…”
Section: Discussionmentioning
confidence: 99%
“…They determined success rate of 93.3% by primary repair of VVF by Transabdominal and transvaginal route combined. 19 A study conducted in UK concluded that there is no difference in success rate of VVF repair done via any one of two approaches transabdominal or transvaginal approach and transvaginal approach is more cost effective than transabdominal approach. 20…”
Section: Discussionmentioning
confidence: 99%